Dynamic contrast-enhanced ultrasound (CEUS) after open and minimally invasive locked plating of proximal humerus fractures - Fischer, Christian; Frank, Marion Kerstin; Kunz, Pierre; Tanner, Michael Christopher; Weber, Marc-André; Moghaddam-Alvandi, Arash; Schmidmaier, Gerhard; Hug, Andreas (Injury, 2016)
Introduction Closed reduction and locked plate fixation of proximal humerus fractures with the minimally invasive deltoid-splitting approach intends to minimize soft tissue damage although axillary nerve injury has been reported. The aim of this study was to assess the deltoid muscle perfusion with dynamic contrast-enhanced ultrasound (CEUS) as novel technique and evaluate its relation to the functional and neurologic outcome after open (ORIF) and minimally invasive (MIPO) fracture fixation. Patients and methods 50 patients, 30 with deltopectoral ORIF and 20 with deltoid-splitting MIPO approach were examined 6-49 months after surgery. Only patients with a healthy, contralateral shoulder were selected. Shoulder function, satisfaction as well as psychosocial outcome were assessed with established scores (Constant, DASH, Simple Shoulder Test, ASES, SF-12). Electromyography (EMG) of the deltoid muscle was performed to determine axillary nerve damage. Ultrasound of both shoulders included CEUS and Power Doppler after deltoid muscle activation via active abduction for two minutes. Results None of the examinations and scores showed significant differences between ORIF and MIPO patients, the psychosocial outcome was similar. The fracture types were equally distributed in both groups. The normalized Constant Score was 76.3±18.6 in the ORIF and 81.6±16.1 in the MIPO group (p=0.373). Deltoid muscle perfusion in CEUS and Power Doppler revealed no differences between both approaches. EMG excluded functionally relevant axillary nerve injuries. Compared with the contralateral shoulder, Constant- and ASES-Scores (p≤0.001 for both ORIF and MIPO) as well as the deltoid CEUS perfusion (ORIF p=0.035; MIPO p=0.030) were significantly worse for both approaches. Conclusions Convincing consensus of functional, ultrasonographic and neurologic examinations demonstrated comparable outcomes after deltopectoral and deltoid-splitting approach. The quantification of the deltoid muscle perfusion with CEUS indicates that the proclaimed benefits of the MIPO approach on soft tissue might not be as great as expected.